Diabetic endothelial microangiopathy and pulmonary dysfunction - Zhang, Lanlan; Jiang, Faming; Xie, Yingying; Mo, Yan; Zhang, Xin; Liu, Chuntao (Frontiers in Endocrinology, 2023)
Diabetes is a widespread metabolic condition with a high global morbidity and death rate that affects the whole body. Inflammatory lung diseases also impose a severe financial burden on global healthcare. Their primary consequences are mostly caused by the macrovascular and microvascular bed degradation brought on by metabolic, hemodynamic, and inflammatory variables. However, research in recent years has expanded the target organ in type 1 and type 2 diabetes to include the lung. Diabetes has long been recognized as significant comorbidity that influences the course of various respiratory disorders and their disease progress. The pathogenesis of the glycaemic metabolic problem and endothelial microangiopathy of the respiratory disorders have garnered more attention lately, indicating that the two ailments have a shared history. This review aims to outline the connection between diabetes endothelial cell dysfunction and concomitant respiratory illnesses, including COVID-19, asthma, and chronic obstructive pulmonary disease（COPD）, in terms of causation and therapy since the exact association between lung disease and diabetes is still unclear.